الإدارة المتكاملة للموارد المائية في حوض نهر مرقية باستخدام برنامج WEAP - حايك شريف; عمار غطفان; عيسى شادي (Latakia University Journal -Engineering Sciences Series, 2018)
The studied area forms a part of the coastal basin on the east coast of the Mediterranean Sea located north of Tartous city. The area is bordered by the Mediterranean Sea from the west, (Jobar, Banias, Albasia) rivers from north and Al Housen river from the south. The area covers about (303) km2. The research aims to implement an integrated management of available water resources within the studied basin, using weap21 program, through the modeling of the Sources of supply and areas of demand within the basin considering year (2010-2011) as the reference year for the study. Research methodology based on collecting data and proposing three scenarios in year 2030.The study found low water requirement by 1.6 M.m3 / year when applying the lower rate of population growth scenario, and increase the water requirement by 5.82M.m3 / year when applying the scenario of high population growth rate, and increase the water requirement by 3.33M.m3 / year when applying the scenario of increased irrigated agricultural land area, as a result of the availability of groundwater is cover all water needs of these scenarios. تشكل منطقة البحث جزءاً من حوض الساحل على الساحل الشرقي للبحر المتوسط، وتقع شمال مدينة طرطوس. يحدها من الغرب البحر المتوسط ومن الشمال أنهار(جوبر–بانياس–الباصية) ومن الجنوب نهر الحصين، وتبلغ مساحة منطقة البحث حوالى303km2. يهدف البحث إلى تنفيذ إدارة متكاملة للموارد المائية المتاحة ضمن حوض نهر مرقية، باستخدام برنامج weap21، من خلال نمذجة مصادر التزويد ومناطق الاحتياج ضمن الحوض واعتماد العام الهيدرولوجي (2010-2011) كسنة مرجعية للدراسة. اعتمدت منهجية البحث على تجميع البيانات واقتراح ثلاثة سيناريوهات في عام 2030، توصلت الدراسة إلى انخفاض الاحتياج المائي بمقدار 1.6 M.m3/year عند تطبيق سيناريو انخفاض معدل النمو السكاني، وزيادة الاحتياج المائي بمقدار 5.82 M.m3/year عند تطبيق سيناريو ارتفاع معدل النمو السكاني، وزيادة الاحتياج المائي بمقدار 3.33M.m3/year عند تطبيق سيناريو زيادة مساحة الأراضي الزراعية المروية، ونتيجة لتوافر المياه الجوفية يتم تغطية كافة الاحتياجات المائية لهذه السيناريوهات.